Acclimation of Ribulose Bisphosphate Carboxylase and mRNAs to Changing Irradiance in Adult Tobacco Leaves: Differential Expression in LSU And SSU mRNA - Prioul, Jean-Louis (1987)
The transfer of Nicotiana tabacum plants grown in low light (60 micromoles quanta per square meter per second) to higher light (360 micromoles quanta per square meter per second) was previously shown to induce adaptive stimulation of photosynthetic capacities. The variations of ribulose bisphosphate carboxylase/oxygenase (RubisCo) expression in mature leaves was examined as a result of this acclimation. Maximum or initial activities increased markedly after low- to high-light transfer with a maximum effect after 2 to 3 days. The higher activity is mainly explained by RubisCo protein synthesis as shown by immunorocket technique. Small subunits of RubisCo (SSU) mRNA relative content determined by hybridization of total RNA with DNA probe by Dot-blot method, followed the same pattern as RubisCo quantity. The magnitude of this response was amplified when more contrasting light conditions (25 versus 360 micromoles per square meter per second) were established on the same leaf: RubisCo activity, RubisCo protein, and SSU mRNA contents decreased in the shaded zone and increased in the high-light zone within 1 day. After 2 days the shade/light ratio was 1 to 3 for RubisCo protein and 1 to 4 for SSU-RNA, whereas the ratios remained equal to one in controls. Hybridization of the same RNA extracts with large subunits of RubisCo (LSU) probe showed no variation in LSU-RNA content. So in green adult leaves, the expression of SSU and LSU genes is regulated differently. The observed white light quantitative effect on RubisCo expression was not dependent on the photosynthetic rate or assimilate content since low CO(2) concentration around the leaf after the light shift did not modify the response.